The RNA helicases Dbp2 and Mtr4 regulate the expression of Xrn1-sensitive long non-coding RNAs in yeast - Wery, Maxime; Szachnowski, Ugo; Andjus, Sara; de Andres-Pablo, Alvaro; Morillon, Antonin (Frontiers in RNA Research, 2023)
The expression of yeast long non-coding (lnc)RNAs is restricted by RNA surveillance machineries, including the cytoplasmic 5'-3' exonuclease Xrn1 which targets a conserved family of lncRNAs defined as XUTs, and that are mainly antisense to protein-coding genes. However, the co-factors involved in the degradation of these transcripts and the underlying molecular mechanisms remain largely unknown. Here, we show that two RNA helicases, Dbp2 and Mtr4, act as global regulators of XUTs expression. Using RNA-Seq, we found that most of them accumulate upon Dbp2 inactivation or Mtr4 depletion. Mutants of the cytoplasmic RNA helicases Ecm32, Ski2, Slh2, Dbp1 and Dhh1 did not recapitulate this global stabilization of XUTs, suggesting that XUTs decay is specifically controlled by Dbp2 and Mtr4. Notably, Dbp2 and Mtr4 affect XUTs independently of their configuration relative to their paired-sense mRNAs. Finally, we show that the effect of Dbp2 on XUTs depends on a cytoplasmic localization. Overall, our data indicate that Dbp2 and Mtr4 are global regulators of lncRNAs expression and contribute to shape the non-coding transcriptome together with RNA decay machineries.